Studi Etnobotani Bahan Kerajinan Masyarakat Nias Selatan dan Pemanfaatannya Sebagai Upaya Pelestarian Budaya Lokal - Nofamataro Zebua; Jerry Samuel Zagoto; Ester Novi Kurnia Zebua; Dedi Yusman Ndruru; Dorotea Trivina Sisokhi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The Nias tribe as a society that is diverse in culture and biodiversity in it holds various phenomena that we need to explore. It is known that the community, especially in South Nias, utilizes many plants as handicraft materials. We conducted this research with the aim of knowing the types of local plants used as handicraft materials and how to process them. The method we used was a qualitative method using data collection techniques such as; observation, structured interviews, and documentation. The data analysis technique used is through data reduction, data presentation, and conclusion drawing. Based on the results and findings of the research conducted, there are around nine types of plants that are utilized by the people of South Nias as handicraft materials. We conclude that the study of ethnobotany as a handicraft material for the people of South Nias has become an ancestral tradition and is a hereditary legacy.